Correlation of Endometrial Thicknessby Transvaginal Sonography with Histopathological Examination in Abnormal Uterine Bleeding in Perimenopausal Age Group - Sah, Sadhana; Dangal, Ganesh; Jha, Meena (Journal of Nepal Health Research Council, 2023)
Background: Transvaginal sonography and endometrial biopsy are the two diagnostic tests, most frequently used to investigate the cause of abnormal uterine bleeding.The aim of this study is to correlate the findings between transvaginal sonography and histopathology for diagnostic evaluation in perimenopausal women with abnormal uterine bleeding.Methods: A descriptive observational study was carried out at Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu, Nepal during the period of one year (1st January 2019 to 30th December 2019) in 70perimenopausal women with abnormal uterine bleeding. Transvaginal sonography wasdone and endometrial thickness was noted. Endometrial biopsy was done under intravenous anaesthesia. Histopathological reports reviewed and analysis done. Results: The most common age group of women presenting with abnormal uterine bleeding was 40 to 43 years(42.9%) and the commonest clinical feature was menorrhagia (50%) followed by menometrorrhagia (27.1%). The transvaginal sonography showed that majority of women had endometrial thickness of 10-12mm(35.7%) followed by 7-9mm(27.1%). Proliferative endometrium (37.1%) was most common histopathologicalfinding followed by secretory endometrium (30%). 10 cases of proliferative endometrium was seen at ET 7-9mm and 1 case of endometrial carcinoma was seen at ET 13-15 mm with P-value <0.13.Conclusions: Transvaginal sonography and histopathological examination are the standard diagnostic procedures for the assessment of abnormal uterine bleeding and for early detection of precancerous lesion like endometrial hyperplasiaand endometrial cancer. Keywords: Abnormal uterine bleeding; histopathology; transvaginal sonography